'Never say never': the first successful management of a type A aortic dissection in Liberia. Issue 1 (31st January 2019) - Swift, Callum Patrick; Ekyinabah, Emmanuel; Graglia, Sally; Adeiza, Mukhtar Abdulmajeed
Abstract : The West African country of Liberia ranks as one of the lowest in the world in most measures of health. The diagnosis and management of complex surgical cases such as aortic dissection is extremely challenging, for reasons ranging from lack of diagnostic imaging capabilities to the high resources required for definitive surgical intervention. We present the first known successfully managed case of aortic dissection in the country's history and with it highlight the challenges faced and a number of lessons learned that are beneficial to anyone working in resource-limited environments.